DEVELOPMENT AND RESEARCH OF A FUNCTIONAL DRINK WITH THE ADDITION OF PEPPERMINT EXTRACT - G. Ag. Hamatgaleeva (Современная наука и инновации)
The modern food market is regularly replenished with new functional food products. When selling food products, it is important to consider that the larger the range of tastes on offer, the better for their implementation. The most convenient object for experiments in the field of raw material composition is drinks. First of all, this allows you to introduce a reasonable choice of ingredients, which positively affects not only the sensory indicators of the drink, but also effectively affects the strengthening of the protective functions of the human body. Secondly, the introduction of a functional ingredient into the raw material composition of the beverage does not require fundamental changes in the technological process. These drinks include mineral table water.  Mineral table water is characterized by a special chemical composition and physicochemical properties, has a remarkable healing and therapeutic effect. One of the characteristic features of the chemical composition of mineral water is the presence of minerals containing carbon dioxide, due to the fact that heavy metals in the earth's crust migrate with hydrocarbons in the form of hydrocarbons, since groundwater is saturated with CO2 [6]. Consumption of mineral canteen water for its intended purpose requires strict adherence to the regime, as well as the study of its chemical composition and organoleptic quality. The introduction of vegetable raw materials into the mineral table water allows to improve the organoleptic characteristics and the ingredient composition of the drink, as well as to provide the human body with the necessary vitamins. The aim of the study was to develop the technology and formulation of a drink based on mineral table water using peppermint extract. In the course of the research, a technology and a formulation were developed, and sensory quality indicators were determined. The developed formulation of a functional drink allows obtaining a product enriched with useful macronutrients, which can be recommended for widespread use. At the same time, high organoleptic characteristics of the developed drink are preserved. The mint flavor of the drink promotes better absorption of mineral water. The drink has a beneficial effect on the human body, due to the balanced mineralization of drinking water.